Comparison between the use of Vitamin D supplement by 20-49 year old women and their nutrition and depression status - Çukurovalı Soykurt, Seniha; Tayfur, Muhittin; Çelen, Emine (Progress in Nutrition, 2021)
ABSTRACT Objective: Aim of this study is to determine the possible relation between the nutritional status, food choices, eating habits, and Vitamin D supplement use of pregnant women between 20-49 years of age, and depression.Methods: The study was conducted between December 2018 and January 2019, on a total of 150 pregnant women between the ages of 20 and 49, who were admitted to Ankara Atatürk Training and Research Hospital Obstetrics and Gynaecology Policlinic. A questionnaire was used in order to identify personal data of the individuals, levels of serum Vitamin D, depression status, physical changes and other information regarding the changes in food consumption. Dietary habits and food consumption records of the individuals were obtained through face-to-face interviews.Results: A total of 75 individuals participating in the study used Vitamin D, while the other 75 did not. Of the individuals participating in the study, beck depression score median of those who used Vitamin D was found as 9.00 (IQR =6), while it was 33.00 (IQR =13) for those who did not. When the scores were analyzed based on Vitamin D use, it was found that there were statistically significant differences.Conclusions: There is evidence from epidemiological studies that show that vitamin D deficiency or insufficiency is associated with depression. Therefore, it is appropriate to recommend taking vitamin D supplements to prevent or treat depression in risk groups. Larger studies are needed to examine this situation in detail.Key words: Nutritional status, Vitamin D, Pregnancy, Depression, Dietary habits